Atraumatic versus traumatic lumbar puncture needles: a systematic review and meta-analysis protocol. Issue 3 (31st March 2017) - Nath, Siddharth; Badhiwala, Jetan H; Alhazzani, Waleed; Nassiri, Farshad; Belley-Cote, Emilie; Koziarz, Alex; Shoamanesh, Ashkan; Banfield, Laura; Oczkowski, Wieslaw; Sharma, Mike; Sahlas, Demetrios; Reddy, Kesava; et al.
Abstract : Introduction: Lumbar puncture is one of the oldest and most commonly performed procedures in medicine, used to diagnose and treat disease. Headache following lumbar puncture remains a frequent complication, causing significant patient discomfort and often requiring narcotic analgesia or invasive therapy. Needle tip design has been proposed to affect the incidence of headache postlumbar puncture, with pencil-point 'atraumatic' needles thought to reduce its incidence in comparison to bevelled 'traumatic' needles. Despite this, the use of atraumatic needles and knowledge of their existence remains significantly limited among clinicians. This study will systematically review the evidence on atraumatic lumbar puncture needles and compare them with traumatic needles across a variety of clinical outcomes. Methods and analyses: We will include published randomised controlled trials (RCTs), observational studies and abstracts, with no publication type or language restrictions. Search strategies will be designed to peruse the MEDLINE, EMBASE, Web of Science, ClinicalTrials.gov, CINAHL, WHO Clinical Trials Database and Cochrane Library databases. We will also implement strategies to search the grey literature. 3 reviewers will thoroughly and independently examine the search results, complete data abstraction and conduct quality assessment. Included RCTs will be assessed using the Cochrane risk of bias assessment tool and eligible observational studies will be examined using the Newcastle-Ottawa Scale. We will examine the outcomes of: headache and its type, intensity, duration and treatment; backache; success rate; hearing disturbance and nerve root irritation. The primary outcome will be the incidence of postdural puncture headache. We will calculate pooled estimates, relative risks for dichotomous outcomes and weighted mean differences for continuous outcomes, with corresponding 95% CIs. Statistical heterogeneity will be measured using Cochran's Q test and quantified using the I 2 statistic. We will also conduct prespecified subgroup and sensitivity analyses to examine if covariates exist and to explore potential heterogeneity. Ethics and dissemination: Research ethics board approval is not required for this study as it draws from published data and raises no concerns related to patient privacy. This review will provide a comprehensive assessment of the evidence on atraumatic needles for lumbar puncture and is directed to a wide audience. Results from the review will be disseminated extensively through conferences and submitted to a peer-reviewed journal for publication. Trial registration number: CRD42016047546.